Making Sense of Workplace Surveillance: How Workers and Union Representatives Experience, Imagine, and Resist Surveillance Exposure - Ollier-Malaterre, Ariane; Parent-Rocheleau, Xavier; Benkrid, Kenza; Provost Savard, Yanick (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2026)
The field of surveillance studies is paying growing attention to workplace surveillance, alongside research on state and police surveillance or other social contexts such as prisons, hospitals, or “smart” cities. As the workplace becomes digitalized, a sharp increase is observed in the prevalence and opacity of employee surveillance technologies, which collect a significant amount of data on their behaviours, performance, attitudes, and emotions. This study, conducted in partnership with Quebec’s three main union confederations, analyzes how workers and union representatives make sense of workplace surveillance and resist it. Drawing on focus groups with thirty union representatives and open-ended survey questions answered by 529 workers, we point out their direct and vicarious experiences of exposure to workplace surveillance. We then analyze the process by which they make sense of their exposure through legitimization, attribution to managerial flaws, and metaphorization and at the same time build dark imaginaries of surveillance fraught with guesses, concerns, and fears about the potential opacity, function creep, persistence in time, and privacy invasion of these technologies. This process shapes seven types of individual and collective responses. We position these responses on a continuum from the least to the most potent in restoring data justice by curbing the deployment and use of workplace surveillance. Responses at the individual level comprise indifference, self-protection, and quitting and carry little potency to restore data justice. Responses at the collective level, however, consisting of sensitization, sousveillance, bargaining, and legal action, show large-scale tangible outcomes.